The challenges of classifying big genera such as Ipomoea - Muñoz-Rodríguez, P; Wood, JRI; Wells, T; Carruthers, T; Sumadijaya, A; Scotland, RW (Wiley, 2023)
Big genera represent a significant proportion of the world's plants. However, comprehensive taxonomic and evolutionary studies of these genera are often complicated by their size and geographic spread. This paper explores the challenges faced in classifying these megadiverse plant groups consequent to the existing tension between diagnosability and increasing levels of resolution from molecular sequence data. We use recent examples from across angiosperms to illustrate how monophyly, diagnosability and completeness interplay with each other in attempts to classify several big genera and, specifically, the genus Ipomoea (Convolvulaceae). Ipomoea and the tribe Ipomoeeae have been the object of recent taxonomic and phylogenetic studies that highlight the limitations of previous attempts to classify the group, and show that the smaller segregate genera traditionally recognised in Ipomoeeae are nested within Ipomoea and are neither monophyletic nor diagnosable. We argue that existing classifications must be abandoned, and that recognising an expanded Ipomoea that incorporates all segregate genera of the Ipomoeeae is the most appropriate solution as it reconciles the properties of monophyly, diagnosability and completeness, and favours nomenclatural stability.